MULTIPLE MACONDO(S): MAGICAL Realist Space and Hybridity - Ahmed Kadhim Aldewan, Mushtaq; Naji Kamil Almousawi, Mokhalad (International Journal of Psychosocial Rehabilitation, 2020)
Macondo, as a setting for Gabriel Garcia Marquez, is one hundred years of solitude, which functions as a hybrid space where the "mappable" and "magical" worlds co-exist simultaneously. As a semi-fictive space, it represents an integral portion of Marquez’s imagination, as well as readers’ perceptions of South America: "Macondo appears in only two of Garcia Marquez’s nine novels and three of his fifty short stories [however] Macondo becomes a kind of shorthand to Latin America," which suggests its significance as a subject for study. For Marquez, a spatial entity is a point of convergence where disparate views interact and can be depicted by separating "the essential elements of a poetic synthesis from an environment." Mendoza states Marquez’s novel, as a magical realist text, proposes mediation between the postmodern and postcolonial. In this sense, Marquez’s perception of the magical real space is partially based upon the belief that art mimetically portrays multiple perceptions of reality.